2009
DOI: 10.1016/j.ijid.2008.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the performance of two liquid-phase culture media for the diagnosis of pulmonary tuberculosis in a national hospital in Lima, Peru

Abstract: The liquid culture medium MGIT was superior to the modified Middlebrook 7H9 and the Ogawa media, both in terms of sensitivity and shorter growing time of colonies of Mycobacterium tuberculosis. The modified Middlebrook 7H9 medium is significantly faster but comparable in diagnostic performance to Ogawa. Costs remain an issue for MGIT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 18 publications
0
15
0
1
Order By: Relevance
“…Moreover, conventional culture methods such as Lowenstein-Jensen (LJ) are slow and have limited impact on therapeutic decision. Modern culture methods on liquid media such as Mycobacteria Growth Indicator Tube (MGIT), are more sensitive and faster [8][10], but have more risk of contamination compared to LJ [11], [12]. Alternative non-commercial rapid culture methods, such as Microscopic Observation Drug Susceptibility (MODS) or Thin Layer Agar (TLA), have recovery rates comparable to other techniques [13]–[18], and might be more suitable to resource-limited settings.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, conventional culture methods such as Lowenstein-Jensen (LJ) are slow and have limited impact on therapeutic decision. Modern culture methods on liquid media such as Mycobacteria Growth Indicator Tube (MGIT), are more sensitive and faster [8][10], but have more risk of contamination compared to LJ [11], [12]. Alternative non-commercial rapid culture methods, such as Microscopic Observation Drug Susceptibility (MODS) or Thin Layer Agar (TLA), have recovery rates comparable to other techniques [13]–[18], and might be more suitable to resource-limited settings.…”
Section: Introductionmentioning
confidence: 99%
“…From the seminal isolation of M. tuberculosis by Robert Koch (10) until today, Ͼ15 different culture media have been developed in order to continuously improve the sensitivity and speed of M. tuberculosis culture, yet only a few media are routinely used today (11). This led to the development of several automated systems employing early growth indicators to accelerate growth detection (12).…”
Section: Discussionmentioning
confidence: 99%
“…The time to detection of a positive culture with MGIT was found to be shorter than with LJ or TLA, in accordance with the results of previous studies. [5][6][7][8][9][10][11][12][13][14] Furthermore, Balabanova et al reported that the concordance between drug susceptibility testing on LJ and MGIT was 96.8% for rifampicin and 95.6% for isoniazid. 28 There are new molecular techniques that perform well, allowing diagnosis on the same day, with the added advantage of providing information about resistance to isoniazid and/or rifampicin.…”
Section: Discussionmentioning
confidence: 99%